Pengaruh Green Innovation Dan Tax Planning Terhadap Nilai Perusahaan - Lingga, Angellee Gloria; Malau, Harman; Susanti, Mila (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
In the face of intensifying corporate competition, organizations must prioritize both profitability and environmental sustainability. The Triple Bottom Line theory is used in this study to emphasize the importance of corporate responsibility in relation to economic, social, and environmental aspects. From 2021–2023, this research looks at the infrastructure businesses listed on the BEI that are part of the infrastructure sector. It looks at how green innovation and tax planning affected their worth. The Price Book Value (PBV) ratio is used in this study to calculate the value of a company using quantitative data analysis. Green innovation and tax planning have a significant effect on company value, according to the report. Green innovation enhances investor confidence through sustainable practices, while strategic tax planning optimizes net earnings and elevates share value. These findings offer critical insights for corporate management in developing sustainable and effective ways to enhance market value.